Flexible and Highly Sensitive Pressure Sensors with Surface Discrete Microdomes Made from Self‐Assembled Polymer Microspheres Array. Issue 11 (11th May 2020) - Zhang, Yuan; Han, Fei; Hu, Yougen; Xiong, Yaoxu; Gu, Han; Zhang, Guoqi; Zhu, Pengli; Sun, Rong; Wong, Ching‐Ping
Abstract: Flexible pressure sensors with high performances are of great interest for smart wearable devices, health monitoring and artificial electronic skins. However, assembling pressure sensors with low cost, simple structure and high sensitivity are still difficult to achieve. Herein, a fast, novel and facile approach is presented to fabricate piezoresistive flexible pressure sensors with surface uniform dome‐like microstructures which are easily replicated from discrete polystyrene (PS) microspheres array by plasma etching the monolayer array of self‐assembly close‐packed PS microspheres. The flexible pressure sensor with dome‐like array (4.2 µm of diameter, 2.1 µm of height and 1.4 µm of spacing) exhibits a high sensitivity of ‐6.61 kPa −1 in the pressure range below 110 Pa, an ultralow detection limit of 1 Pa, a fast response time of 100 ms, and high stability over 3750 cycles of pressure loading/unloading. The sensor is also successfully demonstrated in monitoring human action and beating a drum. Moreover, a 5 × 5 array of the flexible pressure sensor is fabricated to detect spatial pressure distribution. This work provides a simple and effective protocol to build surface microstructures and improve whole performance of flexible pressure sensors, and shows great prospect in the applications of wearable electronics and human‐machine interaction. Abstract : High performance piezoresistive flexible pressure sensor with a high sensitivity of −6.61 kPa −1 (<110 Pa) and excellent stability is fabricated by integrating two polydimethylsiloxane electrodes with size and distance tunable microdomes made from self‐assembled and plasma etched close‐packed polystyrene microspheres array followed by two‐step replication, and exhibits a great prospect in the applications of wearable electronics and human–machine interaction .